Kajian Terhadap Kejahatan Yang Dilakukan Oleh Anak Geng Motor Di Kota Batam - Faizal Fahreza Djuned; Jesen Teo (Fakultas Hukum, Universitas Internasional Batam, 2016)
Crime is an act that violates norms and the rule of law. Nowadays are found that criminal acts not only done by adults only, but children who are still minors are many who commit crimes. Criminal acts by children who are very popular today are a motorcycle gang crime, which the motorcycle gang have already on very disturbing society, from simply using noisy exhaust, to stage a mugging, robbery, and murder. According to the theory of Lambroso, a criminal is someone who has the makings of evil, and the wicked will be genetically inherited meaning derived from generation to generation. Based on interviews, the author in the Police Barelang and Batam City Police Station that the factors that cause crime in the child is young age factor, factor the lack of attention from parents, environmental factors, factors drugs, and factors liquor.